Does Learning Multidisciplinary Field of Biomedical Engineering Help Pandemic of COVID-19? - Shigehiro Hashimoto (Journal of Systemics, Cybernetics and Informatics)

(untitled)
The global community has accelerated the spread of the virus. Medicine alone cannot solve the pandemic. Changes of lifestyle enabled by new technology helps to coexist with viruses. The academic field has been divided into each specialized field. Modern communication tools (internet and cloud databases), on the other hand, promote multidisciplinary academic fields. The multidisciplinary field is not just a collection of fields, but a fusion among fields. Many problems in global society cannot be solved by a single disciplinarian. The global society is waiting for a multi-disciplinarian. For students, it is not easy to find the way to learn a multidisciplinary field. This depends on the curriculum, the textbook, the learning team, and the teacher (the adviser). "Biomedical Engineering" is one of the multidisciplinary fields. It has many related fields: biology, medicine, informatics, and engineering. The topic includes case studies related to COVID-19 in 2020 (education for the undergraduate and the graduate courses in Japan and Thailand) based on the author's experiences: from cross cultural to symbiosis.